Knowledge and Awareness about Nutrition Sensitive Agriculture in Southern Odisha - Mishra, Nibedita; Modak, Satarupa; Padhy, Chitrasena; Ray, Soumik (Indian Journal of Extension Education, 2024)
No matter how nutrition-sensitive agriculture is defined, nutrition starts with what we eat, the products of the food and agriculture sector. It emphasizes how important it is to educate farmers, decision-makers, and the general public on the concepts and methods of nutrition-sensitive agriculture. Programs for education and outreach are essential for promoting awareness of sustainable farming practices and their implementation, which improve nutrition and food security. The present study examines Nutrition-sensitive Agriculture in Southern Odisha, focusing on Gajapati and Rayagada districts. Three blocks were selected from each district, totaling six blocks. Within these blocks, 3 villages were selected randomly from each gram panchayats, so a total of 20 respondents from each block selected by simple random sampling technique to form a total sample size 120. The majority of respondents were having lower (57%) level of knowledge towards nutrition sensitive agriculture with a lower (53%) level of awareness towards nutrition-sensitive agriculture. The regression model explained that 60.5 per cent (R2=0.6050) of variability in influencing the knowledge and 67.04 per cent (R2=0.6704) of variability in influencing the awareness of nutrition-sensitive agriculture.
Keywords: Agriculture; Attitude; Awareness; Knowledge; Nutrition